2017
DOI: 10.1093/jcr/ucx050
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Consumption

Abstract: This paper introduces a new dimension of consumption as liquid or solid. Liquid consumption is defined as ephemeral, access based and dematerialized, while solid consumption is defined as enduring, ownership based and material. Liquid and solid consumption are conceptualized as existing on a spectrum, with four conditions leading to consumption being liquid, solid, or a combination of the two: relevance to the self, the nature of social relationships, accessibility to mobility networks, and type of precarity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
393
3
25

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 333 publications
(431 citation statements)
references
References 89 publications
10
393
3
25
Order By: Relevance
“…These sweeping transformations have unmoored personal identity from its former and unreflexive anchors in tradition (Bardhi et al 2012;Bardhi and Eckhardt 2017;Bauman 2000Bauman , 2007. Rather than being ascribed by tradition and custom, late modernity affords an unprecedented degree of freedom for individuals to choose among "possible worlds" (Giddens 1991, 29) and to pursue a variety of self-defining identity projects, an orientation he refers to as the reflexive project of self.…”
Section: Existential Reflexivitymentioning
confidence: 99%
“…These sweeping transformations have unmoored personal identity from its former and unreflexive anchors in tradition (Bardhi et al 2012;Bardhi and Eckhardt 2017;Bauman 2000Bauman , 2007. Rather than being ascribed by tradition and custom, late modernity affords an unprecedented degree of freedom for individuals to choose among "possible worlds" (Giddens 1991, 29) and to pursue a variety of self-defining identity projects, an orientation he refers to as the reflexive project of self.…”
Section: Existential Reflexivitymentioning
confidence: 99%
“…The consumer research literature has identified that consumers are now expected to address a wide variety of social issues through their individual consumption choices (e.g., global warming, income inequality), whereas in the past these issues would have been addressed structurally by governments, as part of a broader movement of individualization (Bardhi and Eckhardt 2017;Giesler and Veresiu 2014). Giesler and Veresiu (2014) outline how this consumer responsibilization within contemporary neoliberalism is formed by supranational bodies such as the World Economic Forum (http://www.wefor um.org/) through processes of personalization, authorization, capabalization, and transformation.…”
Section: Introductionmentioning
confidence: 99%
“…If firms can begin to understand the types of daily rituals that are more meaningful to the individuals and groups along their customer journeys within the SNS, then the firm can do a better job of designing the platforms around and supporting these practices with the firm's resources, marketing messages, and strategies consistent with production and consumption. These daily rituals are an important part of one's daily social behaviors where the consumer is involved in both consumption and production without focusing on one over the other (Bardhi & Eckhardt, p. 591). This increased knowledge should help to strengthen the web of relationships between the firm's employees/brands and with the SNS consumers—resulting in stronger linkages or connectedness within the SNS, which adds to SRT.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%